PENGEMBANGAN LKPD BERBASIS ASESMEN KOMPETENSI MINIMUM UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA - Zebua, Soniat Mekartini; Harefa , Amin Otoni; Mendrofa, Netti Kariani; Zega, Yulisman (LPPM Universitas Bina Bangsa, 2024)
This research is development research that aims to produce products in the form of LKPD based on Minimum Competency Assessment (AKM) which is valid, practical and effective. This type of research is research development. The development model used is the 4D model. There are four stages in the 4D model are define, design, develop, and disseminate. The data collection instruments used are validation sheets, questionnaires given to experts to find out the feasibility of the product and questionnaires given to experts. given to experts to find out the feasibility of the product and a questionnaire given to students to find out the attractiveness of the product. Given to students to determine the attractiveness of the product. Results validity results obtained from material experts, linguists, and media experts obtained an average of 97.5%, while the practical results of students obtained an average of 92.6%. average of 92.6%, and the effectiveness test results obtained an average of 91.6%. It can be concluded that the AKM-based LKPD is categorized as very valid, very practical, and very effective. valid, very practical, and very effective for improving students' numeracy literacy skills. literacy skills of students.